The Differences requency of Lower Extremities Muscle Strength and Functional Capacity on the difference Supervised Exercise Frequency in Post Cardiac Bypass Graft Surgery - Dewi Nur Fiana; Sunaryo B Sastradimaja; Badai Bhatara Tiksnadi (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Introduction: The optimal time to do exercise in adaptation phase was 36 to 72 hours. Patients with cardiovasculardisease may have an extended adaptation phase to 96 hours and above. It was necessary to know the mosteffective supervised exercise in phase II cardiac rehabilitation between three times/week for 36-hours, and twotimes/week for 96-hours.Method: This study involved 30 patients post-Cardiac Bypass Graft Surgery (CABG) participated in phase IIcardiac rehabilitation at Hasan Sadikin Hospital, Bandung. Subjects divided into two groups; that have done twotimes/week (group 1) and three times/week of the supervised exercised (group 2) for four weeks. The Lowerextremity muscle strength (LEMS) examined by conducting a chair standing test, while functional capacity (FC)evaluated by the 6-minute walking test.Result:Subjects were 58,54±5,90 y.o (group 1) and 61,66±6,36(group 2). The FC and the LEMS before andafter exercise were 10,98 and 15,96 ml/kg(<0,001) on the FC; 7,8 and 12,9 times (<0,001) on the LEMS in group1, besides 9,6 and 14,9 ml/kg(<0,001) on the FC; 8,7 and 13,0 times (<0,001) on group 2,Conclusion. Both groups have increased of the FC and the LEMS after exercise. There were no differencebetween 2 times and 3 times of supervised exercises a week on post CABG pasientsKeywords: coronary artery bypass graft, the frequency of exercise, functional capacity, muscle strength =